Surgical predictors of osteoradionecrosis in irradiated head and neck cancer patients: Jaw resection increases risk whereas neck dissection does not - Hirsch, Julius; Krause, Inga; Tangmanee, Chatpong; Vorwerk, Hilke; Stuck, Boris; Poramate, Pitak-Arnnop; Neff, Andreas (Journal of Stomatology, Oral and Maxillofacial Surgery, 2026)
Introduction: This study investigated the impact of jaw resection (JR) and neck dissection (ND) on the incidence of jaw osteoradionecrosis (JORN) in patients with head and neck cancer (HNC) who underwent head and neck radiotherapy (HNR) involving the jawbone with/without ablative surgery. Evidence on this association remains scarce. Materials and methods: This retrospective study examined irradiated HNC patients treated at a German university hospital between 2007 and 2022, with follow-up until December 2024. The predictor variables were JR and ND, with JORN as the main outcome. Appropriate statistics were computed with a significance level of P ≤ 0.005. Results: Of 510 subjects (22.9 % female; mean age 61.8 ± 11.1 years [range, 14-92]), 14.7 % developed JORN. JR and ND significantly increased JORN occurrence (P < 0.0001; odds ratio [OR], 3.67 [95 % confidence interval [CI], 2.02-6.65]; number needed to harm [NNH], 7.05; post hoc power, 99.7 %). After adjusting for confounders, only JR remained an independent predictor for JORN (OR, 1.16 [95 % CI, 1.08-1.24]; P = 0.0005; Pearson's r for JR = 0.18; Pearson's r for ND = 0.17). JORN rates rose from 6.7 % with HNR alone to 16.5-42.9 % with additional JR and/or ND. Conclusions: JR increases the likelihood of JORN by up to 16 % compared with HNR alone. Approximately one in seven irradiated HNC patients with ablative surgery develops JORN (NNH, 7.05). Increasing the extent of JR and/or ND does not meaningfully affect the risk of JORN (Pearson's r < 0.3).
CRIS-Team Scopus Importer:2025-10-16
Keywords: Jaw disease; Osteoradionecrosis; Surgery